Evaluation of RazakSAT’s S-band link signal measurement with the radar derived rain attenuation - Badron, Khairayu; Ismail, Ahmad Fadzil; Mohd. Ramli, Huda Adibah; Ismail, Maszlan Yusof B.; Ooi, S.T.; Jamil, Siti Farashida (2013)
The initial analysis concerning comparison between measured signal of RazakSAT’s S-band satellite link and radar derived attenuation using an S-band meteorological radar is presented. The S-band (2.23 GHz) satellite-Earth signals of Malaysian RazatSat’s collected at the National Space Agency NSA) space center have been processed and analyzed. The radar data employed was acquired from the Malaysian Meteorological Department’s (MMD) terminal Doppler weather radar installed strategically in the vicinity of Kuala Lumpur International Airport (KLIA). The single-parameter vertical polarization Sband radar reflectivity information was used to calculate the likely rain attenuation along the RazakSAT satellite propagation paths. This was carried out by first converting the radar reflectivity values into rainfall rate using the established Z-R relations of Marshall-Palmer equation and, afterwards, by evaluating the slant path attenuation through the assimilation of the specific rain attenuation derived from the rainfall rate.